2009
DOI: 10.1038/sj.bjc.6604936
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker analysis in stage III–IV (M0) gastric cancer patients who received curative surgery followed by adjuvant 5-fluorouracil and cisplatin chemotherapy: epidermal growth factor receptor (EGFR) associated with favourable survival

Abstract: The aim of this study was to analyse the impact of epidermal growth factor receptor (EGFR), thymidylate synthase (TS), dihydropyrimidine dehydrogenase (DPD), thymidine phosphorylase (TP), aurora kinase (ARK) A/B, and excision repair crosscomplementing gene 1 (ERCC1) on the efficacy of adjuvant chemotherapy with 5-fluorouracil and cisplatin (FP) after curative gastric resection. Normal and cancer tissue were separately obtained from gastrectomy samples of 153 patients with AJCC stage III -IV (M0) who subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 32 publications
1
42
1
1
Order By: Relevance
“…However, other studies reported discordant results in gastric cancer patients (14,15). TS expression in stage III-IV gastric cancer patients who received curative surgery followed by adjuvant chemotherapy was not associated with clinical outcomes (14).We also previously demonstrated that TS expression was not correlated with chemotherapeutic response or OS in metastatic gastric cancer patients (15) and that TS expression did not exhibit a statistically significant association with OS. Patients with lower TS expression levels exhibited a trend to correlate with a shorter OS compared to those with higher TS expression levels OS (P=0.222).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…However, other studies reported discordant results in gastric cancer patients (14,15). TS expression in stage III-IV gastric cancer patients who received curative surgery followed by adjuvant chemotherapy was not associated with clinical outcomes (14).We also previously demonstrated that TS expression was not correlated with chemotherapeutic response or OS in metastatic gastric cancer patients (15) and that TS expression did not exhibit a statistically significant association with OS. Patients with lower TS expression levels exhibited a trend to correlate with a shorter OS compared to those with higher TS expression levels OS (P=0.222).…”
Section: Discussionmentioning
confidence: 73%
“…A previous meta-analysis also reported an HR of 1.35 for a high TS expression in 2,610 patients with localized colorectal cancer (13). However, other studies reported discordant results in gastric cancer patients (14,15). TS expression in stage III-IV gastric cancer patients who received curative surgery followed by adjuvant chemotherapy was not associated with clinical outcomes (14).We also previously demonstrated that TS expression was not correlated with chemotherapeutic response or OS in metastatic gastric cancer patients (15) and that TS expression did not exhibit a statistically significant association with OS.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although the criteria for EGFR amplification are not formally established and a wide range of EGFR/CEN7 ratios (1.7-6.0) were used in previous studies [3,5,22,24,26,29,30], the frequency of EGFR amplification did not vary among these studies, which may be attributed to the fact that the EGFR/CEN7 ratio is [10.0 in most patients with EGFR amplification, and a defined cutoff value would not influence the results (Fig. 2).…”
Section: Discussionmentioning
confidence: 92%
“…However, the incidence of EGFR overexpression reported in previous studies varies from 2 % to 81 %, probably the result of differences in antibodies, scoring systems, and observers [4,21,[24][25][26][27][28][29][30][31][32]. In contrast, the frequency of EGFR gene amplification in gastric cancers is consistently less variable (2-7 %), although most of these studies lacked a sufficiently large number of patients or a detailed EGFR GCN examination [3,5,22,24,26,29,30]. The correlation between overexpression and EGFR GCN has not been firmly established.…”
Section: Introductionmentioning
confidence: 95%